Measuring and Assessing Sick Absence from Work: a European Cross‑sectional Study - Antczak, Elżbieta; Miszczyńska, Katarzyna M. (Comparative Economic Research. Central and Eastern Europe, 2023)
This study analyses sickness absence in selected European countries. We suggested and applied three sick‑leave measures: global sickness absence rate, frequency rate, and absolute crude absence rate. To calculate the rates, open access data from Eurostat, the OECD, and the WHO were used. On the one hand, assessing sickness absence is a challenge in spite of accessible numbers of people and days of absence in public and employer registers. Simultaneously, a detailed understanding of sickness benefits and sick‑pay schemes is needed to elucidate cross‑country differences in sick‑leave rates. The long‑term dynamic trajectory (1970–2020) and regional differentiation effects on absenteeism among countries were considered. Using correlation coefficients and one‑way analysis of variance, a robustness check was performed, and the limitations of the proposed approach to measuring absenteeism were presented. The results evidence that the aforementioned indices present a unique and valid approximation to evaluate and monitor the state of sick absence and inequality in national policies.